2018
DOI: 10.1177/2515690x18762745
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reiki Versus Physiotherapy on Relieving Lower Back Pain and Improving Activities Daily Living of Patients With Intervertebral Disc Hernia

Abstract: Patients with intervertebral disc herniation (IVDH) seek complementary and conventional medical therapies to manage related problems. This study aimed to determine the effectiveness of Reiki compared with physiotherapy to relieve the lower back pain intensity and to improve the activities of daily living (ADL) in the IDVH patients. In this clinical trial study, 60 patients with IVDH were randomly assigned to one of the Reiki, physiotherapy, and drug therapy groups. The severity of pain and the ADL were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
(43 reference statements)
2
5
0
1
Order By: Relevance
“… 1 , 3 The current mainstay of treatments to combat LBP are split into pharmacological (opioids, non‐steroidal anti‐inflammatory drugs, antidepressants) and non‐pharmacological (physical therapy, exercise, massage and manipulation, and alternative therapies (acupuncture, magnet therapy, and reiki). 4 , 5 , 6 , 7 , 8 Although these treatments are potentially helpful in acute LBP, there are limited therapies that are efficient in the management of chronic LBP. 9 , 10 , 11 , 12 For example, treatments available to relieve chronic LBP and recurrent onset back pain include an invasive operation to remove the IVD and potentially fuse adjacent vertebrae, which can lead to the alteration of the normal physiological and biomechanical function of the spine.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 3 The current mainstay of treatments to combat LBP are split into pharmacological (opioids, non‐steroidal anti‐inflammatory drugs, antidepressants) and non‐pharmacological (physical therapy, exercise, massage and manipulation, and alternative therapies (acupuncture, magnet therapy, and reiki). 4 , 5 , 6 , 7 , 8 Although these treatments are potentially helpful in acute LBP, there are limited therapies that are efficient in the management of chronic LBP. 9 , 10 , 11 , 12 For example, treatments available to relieve chronic LBP and recurrent onset back pain include an invasive operation to remove the IVD and potentially fuse adjacent vertebrae, which can lead to the alteration of the normal physiological and biomechanical function of the spine.…”
Section: Introductionmentioning
confidence: 99%
“…Reiki has also been found to be useful in the management of a variety of other chronic and acute conditions. Reiki reduced pain and anxiety in women hospitalized for obstetrical and gynaecological conditions [ 15 ], reduced pain and fatigue in haemodialysis patients [ 16 ], and was as effective as physiotherapy in managing pain in patients with intervertebral disc herniation [ 17 ]. A review found that Reiki was better than a placebo for reducing pain, anxiety, and depression, and improving self-esteem and quality of life in a variety of chronic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several scientific studies show health benefits of Reiki therapy, such as: pain relief (6)(7)(8)(9) , the reduction of stress and anxiety (9)(10) , better coping with illness and therapeutic processes (11) , decreased blood pressure (9) , improvement of depressive symptoms (12) and sleep problems (13) . However, most of these studies have methodological designs that make little room for the expression of the centrality of the subject in the care process.…”
Section: Introductionmentioning
confidence: 99%